PSYCHOLINGUISTIC ASPECTS OF NEOLOGIZATION - ГАПЧЕНКО, Олена (Київський національний університет імені Тараса Шевченка, Навчально-науковий інститут філології, 2023)
The article is dedicated to the experimental investigation of the neologisms' status in the mental lexicon of the person. The main object of the analysis was the associative reactions of the individuals to the new loanwords, which are often used in mass media speech, gathered during the conduction of the free association experiment. The focus is on the investigation of the neologisms' semantics, types of associative connections, and features of the functioning of these units from the aspect of psycholinguistics and linguistic and cultural studies. Psycholinguistic aspects of the process of neologizing and strategies to identify the new word's meaning are observed. An experimental study proves that the perception of neologisms occurs with the use of universal identification strategies. A new word as a unit of a person's internal lexicon wants to comprehend new realities that are in constant dynamics, which are a means of access to the individual's information base and requires comprehensive research. Learning a new word plays an important role in restructuring the connections between the units of the speaker's lexicon. Its renewal takes place to develop the knowledge of new associative connections, to restructure, to occur the new individual contents, and to fill a single vocabulary with new perceptual-affective contents. Neologisms that are in the final stages of assimilation by the recipient language have more varieties of associative reactions than little-used neologisms stimulus. When analyzing the results of the experiment, a distinction should be made between a neologism of its own and a word that is simply new to the speaker and that has not occurred before in individual speech experience. The analysis of the results of the experiment shows that the objective novelty of neologisms does not always coincide with the subjective novelty of stimuli perceived by informants. The internal form plays a significant role in the perception and understanding of neologisms. All the diverse information carried by a new language unit interacts with a complex system of individual and collective norms and assessments, their frequency and scope of use, and the age of acquisition and is stored with a certain set of strategies.

Стаття присвячена експериментальному дослідженню статусу неологізмів в індивідуальному лексиконі людини. Нове слово як одиниця індивідуального лексикону людини є засобом доступу до її інформаційної бази і потребує всебічного дослідження, оскільки засвоєння нового слова відіграє важливу роль у переструктуруванні зв'язків між одиницями індивідуального лексикону. За рахунок розвитку нових асоціативних зв'язків, переструктурування знань, появи нових індивідуальних смислів, наповнення одиниць лексикону новим перцептивно- афективним змістом відбувається його оновлення. Увагу зосереджено на вивченні семантики неологізмів, видів асоціативних зв'язків і особливостях функціонування цих одиниць із позицій психолінгвістики й лінгвокультурології. Розглядаються психолінгвістичні аспекти неоло- гізації, стратегії ідентифікації значення нового слова. Основним об'єктом аналізу були отримані під час вільного асоціативного експерименту асоціативні реакції мовців на нові запозичення, які часто використовуються в мові українських засобів масової інформації. ____________ СПИСОК ВИКОРИСТАНИХ ДЖЕРЕЛ Активні ресурси сучасної української номінації: Ідеографічний словник нової лексики / Є. А. Карпіловська, Л. П. Кислюк, Н. Ф. Кли- менко, В. І. Критська, Т. К. Пуздирєва, Ю. В. Романюк; відп. ред. Є. А. Карпіловська. К. : ТОВ "КММ", 416 с. Віняр Г. М., Шпачук Л. Р. Словник новотворів української мови. Кривий Ріг, 126 с. Вплив суспільних змін на розвиток української мови: Монографія / Є. А. Карпіловська, Л. П. Кислюк, Н. Ф. Клименко, В. І. Критська, Т. К. Пуздирєва, Ю. В. Романюк; відп. ред. Є. А. Карпіловська. К. : Видавничий дім Дмитра Бураго, 444 с. Мазурик Д. Нове в українській лексиці. Словник-довідник. Львів: Світ, 130 с. Клименко Н. Ф., Карпіловська Є. А., Кислюк Л. П. Динамічні процеси в сучасному українському лексиконі: Монографія. К. : Видавничий Дім Дмитра Бураго, 336 с. Колоїз Ж. В. Тлумачно-словотвірний словник оказіоналізмів. Кривий Ріг: ТОВ "ЯВВА", 168 с. Мазурик Д. Нове в українській лексиці : словник-довідник. Львів : Світ, 130 с. Нелюба А. Лексико-словотвірні інновації (1983-2003). Харків, 2004. 188 с. Нелюба А., Нелюба С. Лексико-словотвірні інновації (20042006) : словник. Харків : Майдан, 2007. 144 с. Нові слова та значення : словник / Ін-т укр. мови НАН України; уклали Л. В. Туровська, Л. М. Василькова. К. : Довіра, 2008. 271 с. Нові й актуалізовані слова та значення: словникові матеріали (2002-2010) / Кер. проекту і відп. ред. О. М. Тищенко, авт. колектив: В. О. Балог, Н. Є. Лозова, Л. О. Тименко, О. М. Тищенко; Інститут української мови НАН України. К. : Видавничий дім Дмитра Бураго, 2010. 280 с. Словотворчість незалежної України. 1991-2016: словник / Укладач А. Нелюба. Х. : Харківське історико-філологічне товариство, 2012. 608 с. Стишов О. А. Динамічні процеси в лексико-семантичній системі та в словотворі української мови кінця ХХ ст. (на матеріалі мови засобів масової інформації). Автореф. дис... д-ра філол. наук: 10.02.01. К., 2003. Flares d'Arcetis GR., Sckmsekr R. The process of language understanding: a few issues in cxjffitempomy psycholinguistics. The process of language understanding. Chichester, P. 1-41. Herberg, Dieter: Neologismen der Neunzigerjahren. Neues und Fremdes im Deutschen Wortschatz. Aktueller lexikalischer Wandel. Hrs von G. Stickel. Berlin u.a: de Gryeter, S. 69-104.
ПСИХОЛІНГВІСТИЧНІ АСПЕКТИ НЕОЛОГІЗАЦІЇ
Keywords: neologism; neology; psycholinguistics; associative experiment; verbal associations; lexicon; неологізми; неологія; психолінгвістика; асоціатив¬ний експеримент; мовна особистість; вербальні асоціації; лексикон